Cross-section dependence and the monetary exchange rate model: A panel analysis - Joscha Beckmann; Ansgar Belke; Frauke Dobnik (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
This paper tackles the issue of cross-section dependence for the monetary exchange rate model in the presence of unobserved common factors using panel data from 1973 until 2007 for 19 OECD countries. Applying a principal component analysis we distinguish between common factors and idiosyncratic components and determine whether non-stationarity stems from international or national stochastic trends. We find evidence for a cross-section cointegration relationship between the exchange rates and fundamentals which is driven by those common international trends. In addition, the estimated coefficients of income and money are in line with the suggestions of the monetary model.
Keywords: C32; C23; F31; F41; 330; monetary exchange rate model; common factors; panel data; cointegration; vector error-correction models; Wechselkurs; Makroökonomischer Einfluss; Monetäre Wechselkurstheorie; Kointegration; Schätzung; OECD-Staaten